(untitled) (Global Journal of Management and Business Research, 2025)
The impact of financial obligations within the context of the General Santos City bank employees was studied to determine how it affected work stress, work-life balance, and work commitment. With emerging market dynamics and the evolving employee value proposition, this research filled a relevant gap in the study by exploring the impact of financial obligations on employee well-being and organizational behavior in the banking industry in the locality. Data was collected from a sample of 185 employees from six of the major banks using a quantitative descriptive correlational design. The study found that while financial obligations were low overall, certain debt sources, such as credit card debts and loans, indicated moderate levels. Higher financial obligations had a significant association with increased work stress and decreased work-life balance, but counterintuitively had a positive association with work commitment. These findings highlighted the nuanced effects of financial stressors on overall performance and illustrated the need for organizational interventions directed towards employee well-being and productivity.